Internet censorship detected in Kazakhstan (Kazakhstan) - Voidly (2026)
CRITICAL severity censorship detected in Kazakhstan. Confidence: 65%. Data sourced from CensoredPlanet.
Censorship Incident ID: KZ-2026-0030
Keywords: censorship; KZ; censorship; critical